Nutriacción+: A Tool for Learning About Healthy Eating for Economically and Educationally Vulnerable Children - Diana Arce-Cuesta; Evelyn Pesántez; Pablo Cevallos-Larrea; Cato Van Strijdonck; Michael Peralta (European Journal of Investigation in Health, Psychology and Education, 2025)
Ecuador has a high prevalence of malnutrition. In this scenario, Ecuador promotes education on healthy eating through informative materials and talks. However, their content is usually extensive and does not consider the age, economic status, and educational level of the receivers. In addition, children and adolescents often show little interest in learning about healthy eating. In this regard, the literature points to the use of educational games as an effective alternative to improve attention in learning; however, there are few tools addressed to populations in situations of economic and educational vulnerability. This article presents the development and evaluation of an educational game designed to promote learning about healthy eating for children and adolescents in situations of economic and educational vulnerability in Ecuador. The Design Thinking methodology was applied, with three iterative cycles of design, prototyping, and evaluation. Also, a comparative experiment involving 34 participants was conducted to evaluate the observed differences in knowledge acquisition between Nutriacción+ and informative talks. The results analyze how Nutriacción+ contributes to the learning of healthy eating and offer a replicable game design process for similar populations. The results suggest that Nutriacción+ can improve healthy eating knowledge in children aged 8 to 11 years.